2020
DOI: 10.1002/ese3.740
|View full text |Cite
|
Sign up to set email alerts
|

Physical simulation of upper protective coal layer mining with different coal seam inclinations

Abstract: Protective coal layer (PCL) mining is a preferred regional method for preventing coal and gas outbursts; stress‐relief of PCL mining is the prerequisite of pressure‐relief gas drainage. In order to study the stress‐relief effect of PCL mining on protected coal seams and determine the protection scope of PCL mining under different inclinations, this paper uses physical simulations to study the stress‐relief law and deformation characteristics of the strata during upper PCL mining with a gentle inclination (25°)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to similarity theory, when studying the stress and strain of materials, the test model and material should be geometrically similar to the research object, and the bulk density and stress should be similar. [28][29][30][31] 1. Geometric similarity When conducting simulation experiments, the geometric dimensions of the experimental model and the prototype should be similar:…”
Section: Similarity Theorymentioning
confidence: 99%
“…According to similarity theory, when studying the stress and strain of materials, the test model and material should be geometrically similar to the research object, and the bulk density and stress should be similar. [28][29][30][31] 1. Geometric similarity When conducting simulation experiments, the geometric dimensions of the experimental model and the prototype should be similar:…”
Section: Similarity Theorymentioning
confidence: 99%
“…To delve into the mechanism of pressure relief by roof cutting for an RNG, firstly, the overlying rock structure and migration law of the adjacent roadway should be studied to find the source of the high stress in the surrounding rock of the roadway; meanwhile, a physical simulation experiment is an effective method to study the structure and migration law of overburdened rock [23][24][25]. Therefore, in this paper, based on the mechanical roadway of the 121,302 working face in the Kouzidong coal mine, through physical similarity simulation, the overburdened structure and migration law of the RNG are studied.…”
Section: Physical Simulation Experiments Of Pressure Relief By Roof Cutting In An Rngmentioning
confidence: 99%
“…e deformation would tend to decrease as the distance increases and hence the crack initiation and propagation would be limited. Fang et al [17] investigated the effect of the dip angle on the stress relief and deformation of the coal seam during the extraction of the protective coal seam and they concluded that as the dip angle increases, the deformation and damage in the overlying coal seam tend to decrease. Qin et al [18] believed the computational fluid dynamics (CFD) is the optimized method for coal seam gas drainage design.…”
Section: Introductionmentioning
confidence: 99%